Workload Analysis Reveals Excess Operator Capacity and Incentive Requirements: Analisis Beban Kerja Menunjukkan Kelebihan Kapasitas Operator dan Persyaratan Insentif - Shabirin, Muhammad; Putra, Boy Isma (Indonesian Journal of Innovation Studies, 2026)
General Background: Workload measurement is a critical component in manufacturing management to ensure balanced labor allocation and cost control. Specific Background: PT. XYZ, a wooden board manufacturing company, faces high production targets requiring operators to maintain consistent productivity without additional staffing. Knowledge Gap: Although workload analysis is commonly applied to determine optimal workforce levels, limited studies explicitly connect workload measurement results with structured incentive determination in manufacturing settings. Aims: This study aims to calculate operator workload using the Workload Analysis (WLA) method and determine appropriate incentives based on workload exceeding normal capacity. Results: Work sampling revealed productive percentages of 78%–83%, and WLA calculations showed workload levels of 106%–115%, indicating overcapacity conditions. The excess workload ranged from 6% to 15%, forming the basis for incentive allocation proportional to overload levels. Novelty: This study integrates work sampling, allowance calculation based on ILO standards, and workload analysis to establish a quantitative linkage between workload percentage and incentive determination. Implications: The findings provide a managerial framework for incentive policy formulation without increasing the number of operators, supporting cost control while maintaining production targets in manufacturing operations. Keywords: Workload Analysis, Work Sampling, Operator Productivity, Incentive Determination, Manufacturing Operations Key Findings Highlights Operator capacity levels exceeded standard workload thresholds across all stations. Productive activity percentages ranged between seventy-eight and eighty-three percent. Incentive allocation was proportionally calculated from quantified overload values.